Nonlinear inverse heat conduction: Digitally filtered space marching with phase-plane and cross-correlation analyses. (3rd August 2017) - Chen, Hongchu; Frankel, Jay I.; Keyhani, Majid
ABSTRACT: This paper utilizes concepts extracted from phase-plane and cross-correlation analyses for estimating the optimal regularization parameter required by a nonlinear space marching inverse heat conduction method. The regularization parameter for this approach is based on the cut-off frequency used in a low-pass Gauss digital filter for preprocessing the in-depth temperature data. The simulation uses two in-depth thermocouples which are representative of a physical experiment. Numerical results indicate a high level of robustness as the best prediction is extracted from the prediction space over the spectrum of cut-off frequencies. The feasibility and effectiveness of phase-plane and cross-correlation analyses are discussed.